Indigenous Salvia species : an investigation of their pharmacological activities and phytochemistry - Kamatou, Guy Paulin Poungoue (My University, 2008)
The genus Salvia belongs to the family Lamiaceae and encompasses 900 species worldwide of which 26 are found in southern Africa and many of them are used in local traditional medicine. However, the phytochemistry and pharmacological activities of the South African species have not been extensively investigated. The leaf trichome morphology that may be used to distinguish species was investigated with the scanning electron and light microscopy. Both glandular (capitate or peltate) and non-glandular trichomes were identified in all species. The essential oils were isolated by hydro-distillation and analysed by GC and GC-MS methods. The oil yield was relatively low and ranged from 0.004 (S. radula) to 0.50% (S. muirii) (w/w). Major components identified include α-pinene, 1,8-cineole, linalool, limonene, myrcene, β-caryophyllene, spathulenol, β-caryophyllene oxide, viridiflorol, δ-3- carene and α-bisabolol. High performance liquid chromatography analysis was used to identify phenolic compounds in 17 solvent extracts. Betulafolientriol oxide was detected in all species. Rosmarinic acid was only absent in S. verbenaca, while S. garipensis and S. radula were the only species which lacked oleanolic acid/ursolic acid. Various in vitro biological activities were investigated. Nearly all the solvent extracts displayed anti-oxidant activity with IC50 values ranging from 1.61 to 74.50 μg/ml using the DPPH· radical, while the IC50 values ranged from 11.88 to 69.26 μg/ml with the ABTS·+ radical. The solvent extract of S. schlechteri was three times more active than vitamin C. Total phenolic content based on gallic acid equivalents (GAE) revealed the presence of total soluble phenolics in the extract at 45 to 211 mg of GAE dry sample. Almost all the essential oils exhibited promising anti-inflammatory activity (5-lipoxygenase assay) with IC50 values ranging from 22.81 to 77.32 μg/ml. The antimalarial activity was determined using [3H]-hypoxanthine method on the Plasmodium falciparum (FCR-3) strain. The IC50 values of the essential oils ranged from 1.20 to 13.50 μg/ml and were low compared to the solvent extracts (IC50 values ranging from 3.91 to 26.01 μg/ml). Betulafolientriol oxide and salvigenin isolated from S. radula inhibited the growth of malaria parasites with IC50 values of 4.95 and 24.60 μg/ml, respectively. With the exception of S. radula, all the solvent extracts displayed moderate to good activity against Staphylococcus aureus, vii Bacillus cereus, Klebsiella pneumoniae, Escherichia coli and Mycobacterium tuberculosis with the MIC values ranging from 0.03 to 8.00 mg/ml. Four compounds, namely carnosol, 7-O-methylepirosmanol, oleanolic acid and its isomer ursolic acid were isolated from S. chamelaeagnea as the active principles against S. aureus. The solvent extracts of Salvia species were tested for in vitro anticancer activity against human breast adenocarcinoma (MCF-7), colon adenocarcinoma (HT-29) and glioblastoma (SF-268) using the sulforhodamine B assay. The extracts inhibited cell proliferation of all three cell lines to varying degrees, with the IC50 values ranging between 9.69 and 43.65 μg/ml and 8.72 and 59.12 μg/ml against the MCF-7 and SF-268 cell lines, respectively. The IC50 values against the HT-29 cell line ranged from 17.05 to 57.00 μg/ml. The in vitro toxicity profile of 28 samples (17 solvent extracts and 11 essential oils) was evaluated on human kidney epithelial cells using the 3-(4,5-dimethylthiazol-2-yl)-2,5 dimethyl tetrazolium bromide method. The samples displayed some degree of toxicity with IC50 values ranging from 1.79 to 22.9 μg/ml for the essential oils and from 12.12 to 53.34 μg/ml for the solvent extracts. The essential oil composition of S. africana-caerulea, S. africana-lutea and S. lanceolata, collected at the same locality throughout the 2004/2005 growing season, was compared in terms of essential oil yields, chemical composition and biological activities. Mostly quantitative, rather than qualitative variation was observed. Major seasonal fluctuations of certain essential oil compounds were observed in all three species. Variations in biological activities of the solvent extracts over seasons were noted. The biological activities of the solvent extracts of three Salvia species (Salvia africanacaerulea, S. africana-lutea and S. lanceolata) were evaluated in the presence and absence of essential oils. The solvent extract of S. africana-caerulea without essential oil exhibited the best activity against Gram-positive bacteria (MIC value: 0.1 mg/ml), while the solvent extract containing essential oil of S. africana-lutea was the most active against Gramnegative bacteria. The toxicity profile of all three species was significantly higher (P < 0.05) with the solvent extracts containing essential oils. The in vitro biological activities add scientific support to the use of Salvia species in traditional medicine.
Keywords: Salvia; pharmacological activities; phytochemistry